2009
DOI: 10.1158/0008-5472.can-09-0886
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Splice Variant of GLI1 That Promotes Glioblastoma Cell Migration and Invasion

Abstract: The family of GLI zinc finger transcription factors regulates the expression of genes involved in many important cellular processes, notably embryonal development and cellular differentiation. The glioma-associated oncogene homologue 1 (GLI1) isoform, in particular, has attracted much attention because of its frequent activation in many human cancers and its interactions with other signaling pathways, such as those mediated by K-RAS, transforming growth factor-B, epidermal growth factor receptor, and protein k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
212
1
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(236 citation statements)
references
References 26 publications
11
212
1
9
Order By: Relevance
“…Earlier studies have shown that over-expression of GLI1 promotes tumor progression and invasion in a number of tissues (Zhu et al, 2014;Lo et al, 2009). Based on these and similar results, efforts have been made in search of inhibitors of Hedgehog-GLI1 signaling pathway that could be of value for cancer therapy (Mahindroo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that over-expression of GLI1 promotes tumor progression and invasion in a number of tissues (Zhu et al, 2014;Lo et al, 2009). Based on these and similar results, efforts have been made in search of inhibitors of Hedgehog-GLI1 signaling pathway that could be of value for cancer therapy (Mahindroo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Однако, вопреки ожиданию об активном функционировании этой изоформы, GLI1DN характеризуется сниженной способностью перемещаться в ядро и влиять на транскрипцию генов-мишеней. GLI1DN обнаруживается как в обычных, так и в опухолевых клеточных линиях [25]; при этом GLI1DN не обнаружен в наиболее изученной линии клеток глиобластомы человека U87MG [26].…”
Section: белки образующие путь Hedgehogunclassified
“…рис. 2) [26]. В отличие от GLI1, в tGLI1 отсутствует 41 а.о., а в самом белке присутствуют все известные функциональные домены белка GLI1: домен с цинковыми пальцами, домен трансактивации, NLS-домен (сигнал ядерной локализации, от англ.…”
Section: белки образующие путь Hedgehogunclassified
See 2 more Smart Citations